A Training on The Utilization of Generative Artificial Intelligence in English Learning for EFL Teachers of Vocational High Schools - Apoko, Tri Wintolo; Martriwati, Martriwati; Saputra, Dimas Abimanyu (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to implement the utilization of Gen-AI in English learning for EFL teachers of vocational high schools to improve the teachers’ technological competence as well as to unveil their interest in participating in the training. The community service method was training and simulation. The participants of this training were 35 EFL teachers of state and private vocational high schools located in Eastern Jakarta, Indonesia. The data collection was derived from a Google form questionnaire. The quantitative data were then analyzed descriptively by presenting the percentages, and the written reflections were analyzed by data condensation, display, and conclusion. The results of the training showed that most participants felt enjoyable taking part in the program, describing its practicality, its relevance, their confidence, and contributing to higher motivation. Therefore, it could be recommended that EFL teachers should practice using more relevant Gen-AI tools to improve teaching and learning, their confidence, and have more joyful situations in class.